ANALISIS PENGARUH PESAN KELANGKAAN DAN LIVE COMMERCE TERHADAP PERILAKU PEMBELIAN IMPULSIF (Studi Empiris Pada Mahasiswa Pelanggan Marketplace Shopee di Kota Semarang) - Nurul Anisa Rahma; I Made Bayu Dirgantara; Aulia Vidya Almadana Almadana (Diponegoro Journal of Management, 2022)
Today's technological advancement has led to a new paradigm in the business world. A growing number of online businesses are emerging as a result of business sector developments. Developments in business and the increased number of internet users bring changes in consumer behaviors. One of the consumer behaviors desired by marketers when using online media is impulse buying behavior. In order to be able to increase revenue, marketers must be able to create promotional strategies that can make customers purchase quickly. In light of those conditions, this study aims to analyze the effect of scarcity messages and live commerce on impulsive buying behavior in the Shopee marketplace among students in the Kota Semarang. The sample numbers used in this study were 100 respondents aged over 17 years who lived in the city of Semarang and had made purchases through Flash Sale and Shopee Live in the Shopee Marketplace. This research was conducted using non-probability sampling and purposive sampling techniques. The data were processed and analyzed using multiple linier regression analysis with SPSS (Statistical Package for Social Science) version 25. The study's results show that the message of scarcity positively and significantly affects impulsive buying behavior, while live commerce positively and significantly affects impulsive buying behavior.